Application of microneedle arrays in cosmetics: Promises, advances, and challenges - Amarjitsing Rajput; Anuradha Patil; Priyanka Kandhare; Atmaram Pawar (Medicine in Novel Technology and Devices)
Microneedle technology involves skin puncturing and has emerged as an innovative approach for drug delivery and cosmetic applications. MNs offer advantages over traditional injections, such as reduced pain, infection risks, and improved control of drug delivery. Cosmetic products aim to alter or enhance the appearance of the human body, while transdermal drug delivery involves administering drugs via the skin for local or systemic treatment. The use of MNs in combination with cosmetics has shown promise in improving nutrient delivery, skin healing, and penetration of cosmeceuticals. The development of microfabrication technologies has allowed the production of MNs in various sizes, shapes, and materials mainly used for loading cosmetic compounds. Clinical trial studies have explored MNs' clinical potential in drug delivery, diagnosis and administration of cosmeceuticals. The review highlights the superior efficacy of dissolving MNs in enhancing transdermal drug delivery compared to traditional methods, which are currently used by several researchers and evidenced by multiple clinical studies. The current review article compilation encompasses the microneedle in cosmetic delivery and its applications in managing various skin diseases. It differs from earlier available reviews on MNs in several aspects, novelty lies as it describes microneedle applications in cosmetics. It also focuses on recent technologies for transdermal delivery like iontophoresis, sonophoresis, magnetophoresis, electroporation, laser ablation, and jet injectors. It mainly covers the role of MNs in managing various diseases by covering case studies. It also covers challenges, commercial successes, safety measures, regulatory facts, and future perspectives of microneedles in cosmetic delivery. This article highlights the potential of MNs to revolutionize transdermal drug delivery, which will benefit various industries and patients worldwide. Furthermore, this article emphasizes the potential impact of ongoing research and commercialization of MNs.